The Snow White effect: how food colour saturation impacts food likeability and perceived weight - Rocha, Maria Luís Leite (2019)
We live surrounded by colours, either by the objects we see, or by what nature has been busy painting, such as food. Colours can influence consumers' perceptions and behaviours, particularly regarding food perception and selection, as evidenced by numerous studies described in the literature. However, there is a gap in the investigation of one specific colour attribute - colour saturation - and its impact on the psychological mechanisms that impact food preferences. In this experimental study we investigated how colour saturation of foods and objects influences their perceived weight and likeability and explore if there is a mediational effect of the perceived weight on the likeability. Participants (n = 48) were exposed to images of edible (natural and cooked) and inedible products, with two levels of colour saturation (high vs. low), and indicated, on a scale, the likeability and perceived weight of the products. Then, simulations of real consumer situations were introduced, as well as a task to assess the perceived healthiness of some edible products with both levels of colour saturation. Our results suggest that the colour saturation of food, but not of objects, significantly affects the likeability, playing a critical role in food preference, since participants like more highly saturated foods, whether they are natural or cooked. In contrast, colour saturation does not influence the perceived weight, making its mediating effect on likeability unfeasible. Also, there was no significant effect of colour saturation on the perceived healthiness. This research, besides ensuring experimental control and focusing on the colour attribute less explored in the literature, allows, through the results obtained, to inform initiatives that promote, by manipulating the colour saturation of foods, a positive and sustainable impact on our health and environment.